Clonality of localized and metastatic prostate cancer. Issue 3 (May 2016) - Boutros, Paul C.; Fraser, Michael; van der Kwast, Theodorus; Bristow, Robert G.
Abstract : Purpose of review: The influence of the long life-history of prostate cancer on the temporal and spatial variability of the tumour genome is now being elucidated. Multiregion sequencing to identify spatio-genomic differences in prostate tumour mutation profiles combined with computational approaches can map the evolution and transit of tumour cells throughout an individual patient. Recent findings: A series of recent studies have demonstrated that a prostate tumour is often composed of different subclones, with varying genetic similarity. As such, a single biopsy specimen may be insufficient to make accurate clinical predictions from molecular biomarkers, greatly complicating the application of biopsy-based tools for precision medicine. In addition, subclones that arise outside of the primary tumour can seed new metastases and circulate between sites within a patient. Summary: The mutational complexity of multiple tumour clones within the same individual, which respond differently to specific treatments, suggests the need for multimodal interventions.